2023
DOI: 10.3390/insects14090739
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis Reveals Adaptation Mechanisms of Bean Bug Riptortus pedestris to Different Food Resources

Ze-Long Zhang,
Xiao-Jing Wang,
Hai-Bin Lu
et al.

Abstract: The bean bug, Riptortus pedestris (Hemiptera: Heteroptera), poses a significant threat to soybean production, resulting in substantial crop losses. Throughout the soybean cultivation period, these insects probe and suck on various parts of plants, including leaves, pods, and beans. However, the specific mechanisms by which they adapt to different food resources remain unknown. In this study, we conducted gut transcriptomic analyses of R. pedestris fed with soybean leaves, pods, and beans. A total of 798, 690, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In the current study, notable variations in the expression level of RpedOBP37 were observed across different tissues when normalized to the most stable reference genes (EF1 and Actin) as well as an unstable reference gene (SDHA) (Figure 3). The detoxifying protein CYP6, which plays important roles in the response to oxidative stress in insects, demonstrates a wide distribution across various insect species [26]. When the expression levels of target genes were normalized using the most stable reference genes (EF1 and/or Actin), RpedCYP6 exhibited a consistent expression pattern.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In the current study, notable variations in the expression level of RpedOBP37 were observed across different tissues when normalized to the most stable reference genes (EF1 and Actin) as well as an unstable reference gene (SDHA) (Figure 3). The detoxifying protein CYP6, which plays important roles in the response to oxidative stress in insects, demonstrates a wide distribution across various insect species [26]. When the expression levels of target genes were normalized using the most stable reference genes (EF1 and/or Actin), RpedCYP6 exhibited a consistent expression pattern.…”
Section: Discussionmentioning
confidence: 95%
“…The genomic and transcriptomic data of R. pedestris have been published to study its development, chemosensory genes, and insecticide resistance [20,[23][24][25]41,42]. Previous qRT-PCR studies on R. pedestris commonly employed universal reference genes for insect species [23][24][25][26]. Nevertheless, the use of inappropriate ones may result in misinterpretation of data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations